Theorizing or Negotiating the Law?: A Response to Devika Hovell. (2016) - Tzanakopoulos, Antonios
Abstract : Devika Hovell's article is a very welcome and useful contribution to the debate regarding the "accountability" (whatever the term may mean) of international organizations, and the United Nations in particular. The author argues that scholarship has tended to focus on (descriptive) state practice to the detriment of (normative) theoretical appeal, and so the relevant discussion "has received inadequate theoretical attention." In response, she sets out to tell the story of the United Nations being held to account through a highly theorized (and, if I may venture even at the outset, perhaps a bit stylized) scheme of contrasting "instrumentalist, " "dignitarian, " and "public interest" approaches to due process. This she applies to two case studies, one regarding targeted sanctions imposed by the UN Security Council, mainly in the context of antiterrorism; and one regarding the cholera outbreak in Haiti, where the United Nations has been implicated. Hovell critiques both the instrumentalist and dignitarian approaches, which correspond in broad terms to legal action at the international, and the domestic/regional level, respectively, and argues in favor of a "public interest" approach as better reflecting a "value-based" due process.